2018
DOI: 10.1007/s11136-018-1916-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among parents seeking treatment for their child’s functional abdominal pain

Abstract: Physical HRQoL is not impaired in the majority of parents seeking treatment for their child's functional abdominal pain. However, the time demands and worries due to the child's pain deserve specific attention. Psychosocial interventions for a child's FAP should include information provided to the parents about coping with time constraints and emotional impact. Further prospective studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 73 publications
0
17
0
1
Order By: Relevance
“…The above results were confirmed by Sawyer et al who reported that time pressure significantly influenced the occurrence of depression among parents of children with CP [25]; likewise, Roxburgh established that time pressure predicted the occurrence of depression [47]. Increased caregiver burden, associated with a necessity to deal with the child’s disability and health problems, additionally determines the time demand and emotional involvement of the caregiver [48]. Given the above, in order to relieve the caregiver burden and improve parents’ mental health it is necessary to create a more effective social support system comprising family, relatives, and neighbours offering emotional and practical assistance in solving everyday problems.…”
Section: Discussionmentioning
confidence: 59%
“…The above results were confirmed by Sawyer et al who reported that time pressure significantly influenced the occurrence of depression among parents of children with CP [25]; likewise, Roxburgh established that time pressure predicted the occurrence of depression [47]. Increased caregiver burden, associated with a necessity to deal with the child’s disability and health problems, additionally determines the time demand and emotional involvement of the caregiver [48]. Given the above, in order to relieve the caregiver burden and improve parents’ mental health it is necessary to create a more effective social support system comprising family, relatives, and neighbours offering emotional and practical assistance in solving everyday problems.…”
Section: Discussionmentioning
confidence: 59%
“…1,2 But FAP also has a big impact on parents' health and wellbeing. 3 Finally, its high prevalence and impact is also correlated with a high economic impact on society. For example, the economic impact of FAP and irritable bowel syndrome (IBS) in the Netherlands has been estimated to be over 2500 euros a year.…”
Section: Introductionmentioning
confidence: 99%
“…We designed DARWeb, an innovative WBI rooted in the cognitive-behavioral model, to help change maladaptive thoughts and teach effective coping strategies and to help focus on living in accordance with values and objectives. 24,25 Important novel points, with regard to the available literature, include: (1) it is a specific, tailored intervention for children with FAP, (2) it is almost completely self-directed (we only contacted families to send reminders and for technical problems), (3) it involves parents and children to the same degree (seven units for each member of the dyad), and (4) it is oriented toward secondary prevention, addressing important risk factors and focusing on children with non-severe recurrent abdominal pain problems. With our preliminary studies we found that families were quite satisfied with the intervention; they learned several coping strategies (and to give less importance to pain), and pain impact (severity and quality of life) was reduced coping strategies), and helping to focus on living in accordance with values and objectives.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Simultaneously, a study from 2018 showed that the parents were highly strained due to the demands of their role as caregivers to a child with functional abdominal pain. 22 The parents’ behaviour can be seen as operant factors that serve to either increase or decrease adaptive child behaviour. 23 This concern was also raised by the participants in our study, as some parents raised the question of whether their worries about their child’s symptoms might impact the child and maintain their pain.…”
Section: Discussionmentioning
confidence: 99%